Prediksi Permintaan Semen Dengan Metode Fuzzy Time Series - Yosendra Evriyantino; Budi Darma Setiawan; Randy Cahya Wihandika (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Cement is a material that is used as an adhesive for solid materials namely bricks or concrete blocks into a strong and sturdy unit, usually used for making houses, walls, foundations, roads, or other buildings. In Indonesia, cement production is quite high. In 2017, the total cement production in Indonesia has reached 107.9 million tons. However, high cement production in Indonesia is not matched by the number of requests. As a result, Indonesia experienced an oversupply of cement which caused the price of cement in the market to experience a decline. Therefore, research on predicting cement demand needs to be done as a solution for cement producers in estimating the amount of cement that needs to be produced. In this study, discussing the Fuzzy Time Series method used to predict the amount of demand for cement. The data used is data collected from PT. Semen Indonesia from 2006 to 2018 for each month. From the test results, the smallest MAPE error value was obtained at 10.42% with a parameter value of 80 intervals for 24 test data and 96 training data.